(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study is to construct specific physical fitness test for cricket players. The study was delimited to 500 randomly selected state level male cricket players from central zone. Following items constitute specific physical fitness test battery for male cricket players from central zone are Pull-Ups for Arm Strength, Bent Knee Sit-ups for Abdominal Strength, Standing Broad Jump Test for Leg Strength, 30 Meter Dash for Speed, Cooper 12 min Run Walk Test for Endurance Aerobic Capacity, Phosphate Recovery Test for Anaerobic Capacity, Bridge-Up Test for Flexibility, Dodging Run Test for Agility, Six Second Dash Test for Reaction Time, Bass Stick Test for Balance and Coordination.